In Situ Growth of Mushroom‐Shaped Adhesive Structures on Flat/Curved Surfaces via Electrical Modulation - Hongmiao Tian; Yingze Li; Duorui Wang; Qi Chen; Yuanze Jiang; Tianci Liu; Xiangming Li; Chunhui Wang; Xiaoliang Chen; Jinyou Shao (Advanced Science, 2024)
Abstract Gecko‐inspired adhesives have an extraordinary impact on robotic manipulation and locomotion. However, achieving excellent adhesive performance on curved surfaces, especially undevelopable surfaces, is still challenging. This can be attributed to a considerable difference between the fabrication method and practical necessity, i.e., the adhesive structures are generally fabricated on a flat substrate whereas the manipulating surface is curved, resulting in a low adhesive strength. Here, an in‐situ growth strategy is proposed to fabricate mushroom‐shaped structures at micro/nano‐scale via electrical modulation on flat or curved surfaces. Since the adhesive structures are directly grown on target surfaces without a transfer procedure, they exhibit a large contact area and stress uniformity at the interface, corresponding to an excellent adhesive force. A comparison between grown structures using the proposed method and those fabricated using traditional approaches suggests that the adhesive forces are identical for flat testing surfaces, while the difference can be up to 4 times for developable surfaces and even 25 times for undevelopable surfaces. The proposed adhesion strategy extends the application prospects of gecko‐inspired adhesives from flat surfaces to curved ones, composed of developable and undevelopable surfaces, opening a new avenue to develop gecko‐inspired adhesive‐based devices and systems.